2021
DOI: 10.1101/2021.09.29.21264298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A HOME-TREATMENT ALGORITHM BASED ON ANTI-INFLAMMATORY DRUGS TO PREVENT HOSPITALIZATION OF PATIENTS WITH EARLY COVID-19: A MATCHED-COHORT STUDY (COVER 2)

Abstract: Background and Aim: While considerable success has been achieved in the management of patients hospitalized with severe coronavirus disease 2019 (COVID-19), far less progress has been made with early outpatient treatment. We assessed whether the implementation of a home treatment algorithm, designed based upon on a pathophysiologic and pharmacologic rationale, during the initial, mild phase of COVID-19, could effectively reduce hospital admissions. Methods: This fully academic, matched-cohort study evaluated o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…They have confirmed an earlier published one (Kow and Hasan 2021) and a third preprinted article with similar findings (Zhou et al 2021). Interestingly, a large study by Drake et al (2021) has urged policy-makers to review their advice regarding prescribing NSAIDs in COVID-19 and some colleagues have recently suggested that earliest COVID-19 home therapy with NSAIDs may greatly prevent hospitalizations (Consolaro et al 2021;Pandolfi and Chirumbolo 2021). As early mentioned, all these observations and recommendations side with our old one that started since May 2020 when we started to recommend adopting NSAIDs as lifesaving and of choice in COVID-19 management, unless contraindicated due to other reasons or diseases.…”
Section: Kelleni's Protocol Is Safe To Manage Covid-19supporting
confidence: 67%
“…They have confirmed an earlier published one (Kow and Hasan 2021) and a third preprinted article with similar findings (Zhou et al 2021). Interestingly, a large study by Drake et al (2021) has urged policy-makers to review their advice regarding prescribing NSAIDs in COVID-19 and some colleagues have recently suggested that earliest COVID-19 home therapy with NSAIDs may greatly prevent hospitalizations (Consolaro et al 2021;Pandolfi and Chirumbolo 2021). As early mentioned, all these observations and recommendations side with our old one that started since May 2020 when we started to recommend adopting NSAIDs as lifesaving and of choice in COVID-19 management, unless contraindicated due to other reasons or diseases.…”
Section: Kelleni's Protocol Is Safe To Manage Covid-19supporting
confidence: 67%
“…Therefore, these potentially confounding factors should be controlled in the protocol of any comparative multicenter study of different treatment approaches. Equally important will be to take note of the delay of initiation of therapy compared to the onset of symptoms, as this factor seems crucial in determining outcome [ 2 4 , 6 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…In such patients, lacking a widely approved therapeutic strategy and pending evidence-based guidance, the health authorities suggest a “watchful waiting” or “monitoring” of clinical evolution and the use of symptomatic drugs, such as paracetamol or non-steroidal anti-inflammatory agents (NSAIDs), unless there are specific contraindications. However, lack of treatment in the first 72 h or limiting it to symptomatic medications could be risky in many patients, whose disease is destined to progress to more severe forms [ 1 4 ]. Indeed, many patients have a significant increase in D-dimer levels, an indicator of thrombosis, which correlates with a worse prognosis [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, no official proposal reached the attention of leading authorities, as COVID‐19 home therapy would be based on affordable and widely available anti‐inflammatory and anti‐thrombotic drugs to reduce the impact on any socio‐economic burden and reduce hospitalization overload. Recent clinical data, despite someone yet published as a pre‐print, assessed that COX‐2 inhibitors, either commonly purchasable NSAIDs and selective inhibitors, are a better choice to treat COVID‐19 in its early symptomatology 19,156 . Pharmaceuticals such as nimesulide and celecoxib are strongly suggested to greatly reduce the risk of being hospitalized for the patient with early COVID‐19 symptoms 19,156 .…”
Section: Towards a Pharmacological Proposal For Early Covid‐19 Symptomsmentioning
confidence: 99%
“…19,156 Pharmaceuticals such as nimesulide and celecoxib are strongly suggested to greatly reduce the risk of being hospitalized for the patient with early COVID-19 symptoms. 19,156 The proposal should be exerted usually at home, as in the first stages of COVID-19 symptomatology the patient feels pain, discomfort, even cough or dyspnoea and fever while staying at her/his own home. Major recommended NSAIDs may be therefore celecoxib, nimesulide, ibuprofen and indomethacin, 156 taking into account that any protocol considering one of these NSAIDs might include ASA (>44%) and antibiotics such as azithromycin (>48%).…”
Section: Towards a Pharmacological Proposal For Early Covid-19 Symptomsmentioning
confidence: 99%